Exploring Indonesian Female Viewers’ Identity Projection in Thai BL Series - Masrina, Dwi (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
Thai boys’ love (BL) series portray male-male romance relationship with females as their primary target audiences, though the series tend to avoid depicting women. In the series, both male characters known as seme (dominant) and uke (submissive) possess a mixture of masculine and feminine traits. Using their gaze, women have freedom to choose their gaze’s position weather as seme or uke. This article explores how Indonesian women especially Thai boys’ love series fans, perceive their gender identity when given the freedom to engage with Thai boys’ love series. Through an investigation using qualitative survey, this article shows Thai BL series fans, especially Indonesian females tend to pick their gaze as uke, a male submissive character with more feminine features than the seme one, a male dominant character with more masculine trait. However, there are some fans who stand in seme position. Each preference is caused by two main factors: their own gender and how they behave in their love relationship.